How Do Experts Treat Patients with Bullous Pemphigoid around the World? An International Survey - Marine Guignant; Billal Tedbirt; Dedee F. Murrell; Masayuki Amagai; Valeria Aoki; Johannes Bauer; Giuseppe Ciancinni; Donna Culton; Maryam Daneshpazhooh; Dipankar De; Janet Fairley; Russell Hall; et al. (Elsevier, 2022)
Many treatments are currently proposed for treating patients with bullous pemphigoid (BP). We assessed treatment modalities of BP depending on the different countries, BP extent, and patients' comorbidities. We surveyed worldwide experts about how they treat patients with BP. A total of 61 experts from 27 countries completed the survey. Severe and moderate BP were treated with oral prednisone (61.4 and 53.7%, respectively) or superpotent topical corticosteroids (CSs) (38.6 and 46.3%, respectively). Conventional immunosuppressants were more frequently combined with oral prednisone (74.5%) than with superpotent topical CS (37.5%) in severe BP. Topical CSs were mainly used in Europe in mild (81.1%), moderate (55.3%), and severe (54.3%) BP. In the United States of America and Asia, systemic CSs were mainly proposed for treating severe (77.8 and 100%, respectively), moderate (70 and 77.8%, respectively), and also mild (47.1 and 33.3%, respectively) BP. Most experts reduced the initial dose of oral CS in patients with diabetes mellitus (48.1%) or cardiac insufficiency (40.2%) but rarely changed BP treatment in patients with neurological disorders or neoplasia. This survey showed major differences in the way patients with BP are treated between AmeriPac countries (United State of America, Latin America, and Australia) and Asia on the one hand and Europe and the Middle East on the other hand.